Seroprevalence of Neospora caninum infection and associated risk factors in cattle in Shanxi Province, north China - Cao, Hui; Zheng, Wen-Bin; Wang, Yu; Gao, Wen-Wei; Liu, Qing; Zhu, Xing-Quan; Lei, Yu-Ping; Tumen, Bayaer; Song, Hong-Yu (Frontiers in Veterinary Science, 2022)
Neospora caninum is an obligate intracellular parasitic protozoan that can cause abortions in cattle and cause considerable economic losses to the cattle industry. As a major livestock province, little is known of N. caninum infection in cattle in Shanxi Province, north China. In order to investigate the seroprevalence of N. caninum in cattle in Shanxi Province, 978 cattle serum samples were collected from 11 cities in three representative geographical locations in Shanxi Province, and the N. caninum-specific IgG antibodies were examined using an indirect enzyme linked immunosorbent assay (ELISA) kit commercially available. The results showed that 133 of 978 cattle serum samples (13.60%, 95% CI = 11.45-15.75) were positive for N. caninum antibodies, and the seroprevalence in different cities ranged from 0% to 78.89%. The geographical location and management mode were the risk factors related to N. caninum infection in cattle herds in Shanxi Province. Cattle in Northern and Central Shanxi Province as well as cattle whose management mode is that of large-scale cattle farming companies are more susceptible to N. caninum infection. This was the first large-scale survey of N. caninum seroprevalence and associated risk factors in cattle in Shanxi Province, which provided baseline information for the prevention and control of N. caninum infection in cattle in Shanxi Province, north China.